Sosialisasi Pencegahan Demam Berdarah Dengue dan Pemeriksaan Hemoglobin Pada Santri Remaja Pondok Pesantren Darul Falah Al Hasyimiyah, Semarang: Community Education on Dengue Hemorrhagic Fever Prevention and Hemoglobin Screening among Students of Darul Falah Al Hasyimiyah Islamic Boarding School, Semarang - Putri, Gela Setya Ayu; Rauf, Mohamad Jois; Bano, Siti Maryam; Djafar, Hawin Pratiwi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Dengue Hemorrhagic Fever (DHF) is still a significant public health issue in Indonesia, with a high incidence rate. Overcrowded environments, such as Islamic boarding schools, pose a higher risk for the spread of DHF. In addition to environmental factors, anemia in adolescents also increases susceptibility to infection. Therefore, education on DHF prevention and hemoglobin (Hb) screening is essential as promotive and preventive measures. This activity aimed to raise students' awareness of the importance of maintaining environmental hygiene and to identify hemoglobin status as part of early detection of vulnerability to DHF infection. The program was conducted at Darul Falah Al-Hasyimiyah Islamic Boarding School, Semarang, involving 50 adolescent students. Interventions included interactive counseling on DHF prevention, knowledge evaluation through pre-test and post-test, and Hb measurement using a digital Hb meter. Results showed a significant improvement in students' knowledge, with mean pre-test and post-test scores of 46 and 92, respectively (p<0.05). Hb screening revealed that 64% of participants had Hb levels below normal (mean 10.8±1.2 g/dL), indicating a high prevalence of anemia among students. These findings highlight the need for nutritional interventions, balanced diet education, and regular health monitoring. In conclusion, this activity effectively enhanced students' awareness of DHF prevention while simultaneously identifying anemia status. This model can be duplicated in similar areas as a promotional and preventive strategy against environmentally based infectious diseases. Abbreviations are permissible, except for units of amount, and should be used sparingly.